Apoptotic and autophagic effects of Sesbania grandiflora flowers in human leukemic cells. - Rajneeta Roy; Deepak Kumar; Biswajit Chakraborty; Chinmay Chowdhury; Padma Das (PLoS ONE, 2013)
BACKGROUND: Identification of cytotoxic compounds that induce apoptosis has been the mainstay of anti-cancer therapeutics for several decades. In recent years, focus has shifted to inducing multiple modes of cell death coupled with reduced systemic toxicity. The plant Sesbania grandiflora is widely used in Indian traditional medicine for the treatment of a broad spectrum of diseases. This encouraged us to investigate into the anti-proliferative effect of a fraction (F2) isolated from S. grandiflora flowers in cancer cells and delineate the underlying involvement of apoptotic and autophagic pathways. PRINCIPAL FINDINGS: Using MTT based cell viability assay, we evaluated the cytotoxic potential of fraction F2. It was the most effective on U937 cells (IC50∶18.6 µg/ml). Inhibition of growth involved enhancement of Annexin V positivity. This was associated with elevated reactive oxygen species generation, measured by flow cytometry and reduced oxygen consumption - both effects being abrogated by anti-oxidant NAC. This caused stimulation of pro-apoptotic proteins and concomitant inhibition of anti-apoptotic protein expressions inducing mitochondrial depolarization, as measured by flow cytometry and release of cytochrome c. Interestingly, even with these molecular features of apoptosis, F2 was able to alter Atg protein levels and induce LC3 processing. This was accompanied by formation of autophagic vacuoles as revealed by fluorescence and transmission electron microscopy - confirming the occurrence of autophagy. Eventually, F2 triggered caspase cascade - executioners of programmed cell death and AIF translocation to nuclei. This culminated in cleavage of the DNA repair enzyme, poly (ADP-ribose) polymerase that caused DNA damage as proved by staining with Hoechst 33258 leading to cell death. CONCLUSIONS: The findings suggest fraction F2 triggers pro-oxidant activity and mediates its cytotoxicity in leukemic cells via apoptosis and autophagy. Thus, it merits consideration and further investigation as a therapeutic option for the treatment of leukemia.